Between politics and administration: Evidence from Danish local government - Steffensen, Filip Strunge (Politica, 2023)
Studies show that top civil servants in Danish local government emphasize giving political advice. This finding has been used to deduce information about the role that top municipal officials across countries play vis-à-vis politicians. The existing literature has examined this through questionnaires, but in this article, I propose studying role perceptions through interviews, which provide access to thick descriptions of the role of top officials. Through 12 interviews, I show that top municipal officials perceive their role as translators, liaisons and mediators, implying a frequent interaction between the political and administrative level. While officials find it important to serve the political level, it is also a central part of the role perception that they understand themselves as politically neutral. This creates a cross-pressure that officials try to balance by employing three strategies to shield them from inappropriate political interference: They seek advice, educate and restrict access.